The Influence Of Workload And Job Stress On Employee Performance At The Karawang State Attorney's Office - Fitri Nuraini; Sari Marliani; July Yuliawati (PT. Berkah Digital Teknologi, 2024)
Purpose of the study — The purpose of this study is to examine the effect of workload and job stress on employee performance at the Karawang District Prosecutor's Office.Research method—This study employed a quantitative method with correlational research design. Data was collected from 53 employees using validated questionnaires measuring workload, job stress, and performance. Data was then analyzed using SPSS through multiple linear regression analysis.Result— The results showed that workload and job stress positively and significantly influenced employee performance, both partially and simultaneously. Partially, workload had a significance value of 0.001 and job stress was 0.000. Simultaneously, they were significant with a value of 0.000. The determination coefficient was 0.751, meaning 75.1% of performance is influenced by workload and job stress.Conclusion— In conclusion, excessive workload can lead to job stress which negatively impacts employee performance at the Karawang District Prosecutor's Office. Practically, assigning reasonable work duties according to employee capacity and implementing stress reduction programs are recommended.